In vitro hypoglycemic, antioxidant, anti-inflammatory activities and phytochemical profiling of aqueous and ethanol extracts of Helichrysum cymosum - Achasih Quinta Nkemzi; Kunle Okaiyeto; Nasifu Kerebba; Fanie Rautenbach; Omolola Oyenihi; Okobi Eko Ekpo; Oluwafemi O. Oguntibeju (Elsevier, 2024)
Background: Diabetes mellitus (DM) is a complicated and multifaceted metabolic disorder that poses significant health challenges for individuals and healthcare systems worldwide. Efforts to understand its pathophysiology and develop novel treatment options for the disease through preclinical research and drug discovery have been the focus of several researchers globally. One of the approaches to tackle this is the use of plant-based products, which are therapeutically effective and affordable. Purpose: The current study investigated the phytochemical constituents of Helichrysum. cymosum aqueous (AQ) and 70% ethanol (ET) extracts, their cytotoxicity, as well as their in vitro antidiabetic effects via antioxidant, anti-inflammatory, and selected enzyme inhibition assays. Materials and methods: Bioactive compounds were identified using High-Performance Liquid Chromatography and UHPLC-ESI-MS. Cytotoxicity was assessed on C3A hepatocyte cells using MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide). Antioxidant activity was determined using the average cellular CellROX® Orange fluorescent intensity, ferric reducing antioxidant power (FRAP), trolox equivalent antioxidant capacity (TEAC) and 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. The mouse macrophage cell line, RAW 264.7 was used to assess anti-inflammatory activity by measuring the levels of nitrite produced. Enzymatic inhibitory assays such as alpha glucosidase, alpha amylase and pancreatic lipase inhibition were performed to determine the antidiabetic effect of the plant extracts. Also glucose uptake and glucose utilization on C3A hepatocytes and L6myocytes were evaluated. Results: The results show significantly higher polyphenol and flavonol contents in ET (303 ± 4 mg GAE/g, 183 ± 6 mg QE/g, respectively) compared to AQ (83.7 ± 2 GAE/g, 36.0 ± 1 respectively). ET also showed significantly higher antioxidant activity (DPPH assay: 1893 ± 34 µmol TE/g; FRAP assay: 158 ± 2 µmol AEE/g; and ABTS assay: 1402 ± 26 µmol TE/g) compared with AQ (DPPH assay: 606 ± 8.4 µmol TE/g; FRAP assay: 530 ± 2 µmol AEE/g; and ABTS assay: 450 ± 11 µmol TE/g). HPLC reveals the presence of caffeic acid (AQ), chlorogenic acid (AQ and ET), kaempferol (AQ), and rutin (ET), while UHPLC-ESI-MS analysis identified 43 compounds in both AQ and ET. Cytotoxicity was observed only for ET at a concentration of 250 µg/mL, while both AQ and ET exhibited cellular antioxidant activity, alpha-glucosidase activity, and minor alpha-amylase activity. There was also significant glucose uptake and its utilization by C3A hepatocytes and L6 myocyte cells. However, the extracts did not exert substantial effect on lipase inhibition in the current study. Conclusion: The finding reveals that the bioactive compounds present in H. cymosum extracts have potential antioxidant, anti-inflammatory, and hypoglycemic effects; therefore, these compounds can be further explored as future candidates for drug discovery.